Penetapan Target Premi Asuransi Jiwa Syariah untuk Mencapai Titik Impas dengan Pendekatan Model Profit Testing - SOEDIBJO, SUGENG; FITRIATI, RACHMA (UI Scholars Hub, 2011)
This research aimed to give illustration of profit achievement through determination of premium income based on technical assumptions that could be controlled by the company. This model could generally be used as a management tool to take the decision and to arrange the company work planning through allocation of company’s resources. The research was carried out at BRIngin Life Syariah (BLS) company. The results of this study showed that premium income achievement to reach the break even point depended on the kind of insurance products marketed, the operational cost, the investment yield and the risk level of clients. Based on the analyses of profit testing and sensitivity, the product of Tabarru’ produced a better break even point and profit indicator than the insurance products that had the savings element. The results showed that the product of Tabarru with the operational cost between IDR 247,500.0 – IDR302,500.00 per year would reach the break even point between 3.60–5.26 a year. The savings products that had the same operational costs could reach the break even point at 3.91–5.47 a year.